Some Aspects of the Italian Diplomacy Towards the Albanian Republic (1925-1928) - Luku, Esilda (Richtmann Publishing, 2012)
This paper aims to analyze the relations between Italy and Albania during the republican government of the President AhmetZogu (1925-1928). Its approach is based on the study of the documentation, focusing on the factors that influenced the Italian diplomacytowards the Albanian state, as follows: At first, the government of Italy had economic interests in Albania, forcing the political class tomake concessions to search and exploit the oil and mineral reserves from the Italian enterprises, such as: Azienda Italiana Petrolid’Albania (AIPA), Sindaco Italiano Giacamenti Minerari Albanesi (SIGMA) etc; the Italian investments in agriculture and theestablishment in Rome of the National Bank of Albania, in March 1925. Secondly, Italy intended to exert the political influence on Albaniabecause of its strategic position in the Balkan. Rome benefited from the necessity of the President Zogu to protect his political regimeand to overcome the difficult economic situation, forcing the Albanian government to sign the First Pact of Tirana, on 27th November,1926. According to this agreement, Italy would defend the juridical, the territorial and the political status-quo of Albania against everypotential aggression. Also it imposed some restrictions on the foreign policy of Albania, menacing its sovereignty. While, the SecondPact of Tirana signed on 22nd November, 1927, was basically a defensive alliance that strengthened the Italian domination in Albania,using it as a military base for further penetration in the Balkan.Thus, the Italian diplomacy towards the Albanian state with the aim ofachieving its political and economic goals not only posed a threat to the sovereignty of Albania but also to the stability of the region.